Disentangling the IR spectra of 2, 3, 3, 3-tetrafluoropropene using an ab initio description of vibrational polyads by means of canonical Van Vleck perturbation theory. (December 2019) - Pietropolli Charmet, Andrea; Bizzocchi, Luca; Giuliano, Barbara Michela; Caselli, Paola; Craig, Norman C.; Krasnoshchekov, Sergey V.
Highlights: Complete spectroscopic analysis of the IR spectrum of 2, 3, 3, 3-tetrafluoropropene. Accurate determination of absorption cross section data Thorough understanding of polyad mixing in the vibrational spectra. Benchmark of numerical-analytic second order Van Vleck perturbation theory. Graphical abstract: Abstract: The vibrational spectra of 2, 3, 3, 3-tetrafluoropropene (2333TFP) are studied in the infrared experimentally and theoretically by the canonical second-order Van Vleck operator perturbation theory (CVPT2) and full quartic potential energy surface (PES). 2333TFP belongs to hydrofluoroolefins (HFOs) considered among the most promising alternatives to the hydrofluorocarbons presently in use in refrigeration. The medium resolution infrared spectra of gaseous 2333TFP were recorded in the range 9500–30 cm − 1 . The integrated IR intensities for all bands falling between 6300–400 cm − 1 were accurately determined. Theoretical descriptions of up to four-quanta anharmonic vibrational states of 2333TFP are performed using the state-of-the-art numerical-analytic implementation of CVPT2. High quality harmonic frequencies, obtained at different coupled-cluster levels of theory up to the CCSD(T*)-F12c/VTZ-F12 model were combined with the full quartic MP2/cc-pVTZ anharmonic force field to form the hybrid PES. All Fermi and Darling-Dennison resonances were detected using a universal criterion and treated with the variational CVPT2/VCI stage by using two-, three-, and four-quanta harmonic oscillator basis sets. General recommendations for choosing such basis sets in future studies are formulated. In addition to all fundamentals and their resonance satellites, the vibrational analysis led to the assignment of virtually all observed first/second overtone and binary/ternary combination bands. Computed dipole moment first derivatives in the principal axis system yielded reliable predictions of band shapes for fundamental transitions in good agreement with observed counterparts. Computed anharmonic IR intensities showed an excellent agreement with observed data in the measured ranges. The fundamental spectroscopic effect of excited resonances is observed experimentally and explained theoretically as a universal mechanism of formation of vibrational polyads. The efficiency of the CVPT2/VCI approach employed is clearly demonstrated and can be considered as a benchmark for modeling vibrational states and interpretation of vibrational spectra of semi-rigid molecules.